A real-time vehicle routing system for RFID-tagged goods transportation - Li, Feng; Wei, Ying (2008 IEEE International Conference on Service Operations and Logistics, and Informatics, 2008)
This paper proposes an intelligent vehicle routing system on real-time in-transit goods status information and real-time traffic flow information of road network. The system collects and extracts real-time information of in-transit goods by attached active RFID tags. Real-time traffic flow information of observed roads and the vehicle location information are fed back by the driver of cargo. Moreover, traffic flow status of unobserved roads is extracted from historical data as empirical stochastic distributions. Therefore, the optimization of vehicle route is calculated by a simulation-based optimization algorithm. In the algorithm, a computational model is built to represent the complicated vehicle routing problem, instead of traditional mathematical model. In this way, each uncertain traffic flow status of unobserved roads in the problem is simulated by a random variable generator in the computational model. The intelligent algorithm optimizes the vehicle route according to simulation outputs. Additionally, the proposed system is built on multi-agent platform under client/server software architecture. The distributed computing capability of multi-agent technology promises the approach has better operating performances. Finally, a prototype system is implemented to verify our proposal on the simulation platform.